Media Pembelajaran Interaktif Mengetik 10 Jari Berbasis Multimedia SD IT TPI - Audiansyah, Wanda; Atsil, Rayhan Alfatih; Sofianda, Wahyu; ., Taufiqurrahman; Asnawi, Azi; Ikhwan, Ali (Jurnal Sains dan Teknologi (JSIT), 2023)
Interactive multimedia-based media trains students to change a learning process from manual learning methods to interactive methods. In addition to teaching students to be more active, this application is expected to help teachers teach more effectively and efficiently. Based on these problems, explaining information on system weaknesses, how to overcome them and finding the right references about interactive teaching methods. The results of the analysis at SDIT TPI (Islamic Education Park) found that this learning method is still manual. The process of delivering material manually creates an ineffective and efficient teaching and learning system at SDIT TPI (Islamic Education Park) so that students are still dependent on the teacher. Therefore, this media is made as an interactive media based on multimedia teaching and learning activities so that the learning process is not limited by the classroom learning process. Students are expected to study independently outside the classroom.